Analysis of Leadership Model for Participation of River Guard in the River Waste Management System for Sustainable Healty City in Banjarmasin South Kalimantan, Indonesia - Herawati, Herawati; Kausar, Lola Illona Elfani; Arifin, Syamsul; Atqiya, Ilma Hudatil; Rayhan, Muhammad (Scholar Center, 2024)
(1) Background: Health issues in wetland environmental areas, especially the problem of waste in rivers, is still a strategic issue, so it was important to study about river management. Whatever management, it cannot be separated from the leadership aspect, because leadership plays a key role in formulating and implementing strategies policy, including encourage community participation. Thus, community participation becomes an important thing in integrated river management to create a sustainable Healthy City. One element that is part of the community participation is the river guard. This research was aimed to analyze the leadership model for the participation of river guard in the river waste management system in Banjarmasin City; (2) Methods: The research design used mixed methods research (qualitative and quantitative research methods). The research subjects were 30 river guards and other informants who involved of river waste management in Banjarmasin City; (3) Results: The research results showed that the majority of river guards had good participation, and only a few of river guards had sufficient participation. Furhermore, it was found that the Laissez Faire leadership model or style tends to influence the participation of river guards in the river waste management system in Banjarmasin City; (4) Conclusions: The laissez faire leadership style does not always mean negative, but of course there are positive things or effects, when a leader is able to transform it. Keywords: community participation; healthy city; leadership model; river waste management